CYP1A1 activity in rainbow trout is inhibited by the environmental pollutant p-cresol - Burkina, Viktoriia; Sakalli, Sidika; Zlabek, Vladimir; Zamaratskaia, Galia (Environmental toxicology and pharmacology, 2018)
Naturally- and anthropogenically-produced cresols could pose serious risks to fish health. In this study, three piscine CYP isoforms were investigated for their abilities to interact with p-cresol. Therefore, the activity of 7-ethoxyresorufin-O-deethylase (EROD), 7-benzyloxy-4-trifluoromethylcoumarin O-debenzylase (BFCOD), and p-nitrophenol hydroxylase (PNPH) were evaluated in the hepatic microsomes of juvenile rainbow trout. Results showed that EROD activity was inhibited in a competitive manner, BFCOD activity was inhibited in presence the highest tested p-cresol concentration and PNPH activity was not affected. These results indicate that p-cresol might affect the ability of fish to metabolize numerous aromatic hydrocarbons and dioxin compounds, which are present in the aquatic environment.
Keywords: Animals; rybí proteiny; Oncorhynchus mykiss; zvířata; Cresols; chemické látky znečišťující vodu; Water Pollutants, Chemical; cytochrom P-450 CYP1A1; Cytochrome P-450 CYP1A1; Fish Proteins; kresoly